GINGER (ZINGIBER OFFICINALE) SUPPLEMENTATION FOR GLYCEMIC CONTROL IN TYPE 2 DIABETES MELLITUS: A STRUCTURED NARRATIVE REVIEW OF CLINICAL TRIALS (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize clinical trial evidence on the effects of oral ginger on glycemic control in patients with type 2 diabetes mellitus.Methods: This was a structured narrative review. The authors searched PubMed, Scopus, Web of Science, and Cochrane Library through November 2025 to identify randomized clinical trials and relevant meta-analyses. Studies were prioritized if they compared oral ginger with placebo or usual care for at least 4 weeks and reported fasting plasma glucose, HbA1c, or insulin resistance indices. Data were qualitatively synthesized according to formulation, dose, intervention duration, efficacy, and safety.Results: Most randomized controlled trials were small and short-term, mainly using ginger powder capsules at doses of 1.2–3.0 g/day for 8–12 weeks. Some studies reported reductions in fasting plasma glucose and/or HbA1c, whereas others showed more pronounced effects on fasting insulin or HOMA-IR. Extra-glycemic benefits, including improvements in lipid profile, C-reactive protein, or malondialdehyde, were inconsistent across studies. Published meta-analyses also yielded mixed findings. Ginger was generally well tolerated, and adverse events were mainly mild gastrointestinal symptoms.Conclusion: Oral ginger may provide small adjunctive benefits in some patients with type 2 diabetes mellitus. However, current evidence remains limited by small sample sizes, heterogeneous preparations, and short follow-up. Ginger should not be considered a stand-alone glucose-lowering therapy.
Keywords: Ginger; Zingiber officinale; Type 2 diabetes mellitus; Glycemic control; Randomized controlled trial.